2010
DOI: 10.3133/ofr20101086
|View full text |Cite
|
Sign up to set email alerts
|

Channel Maintenance and Flushing Flows for the Klamath River Below Iron Gate Dam, California

Abstract: Figure 11. Annual channel maintenance capacity index (ACMCI) for the Klamath River below Iron Gate Dam, California. The equation for the index is cmci = (QD ^0.87-5000 ft 3 /s ^0.870/(10000 ft 3 /s ^0.87). Data for 1924-1960 were for the streamgage below Copco Dam a short distance upstream from the present streamgage and at a location within the Iron Gate reservoir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…The present sediment discharge of the Smith River is roughly an order of magnitude smaller than the Klamath River (∼ 3.3 × 109 kg yr −1 vs. 0.4 × 109 kg yr −1 ; Wheatcroft and Sommerfield, 2005;California Beach Restoration Study, 2002), opposite to the trend observed offshore. The present difference might be attributed to modern anthropogenic activity (Holmquist- Johnson and Milhous, 2010), mixing of sources on the abyssal plain, or other causes.…”
Section: Discussionmentioning
confidence: 71%
“…The present sediment discharge of the Smith River is roughly an order of magnitude smaller than the Klamath River (∼ 3.3 × 109 kg yr −1 vs. 0.4 × 109 kg yr −1 ; Wheatcroft and Sommerfield, 2005;California Beach Restoration Study, 2002), opposite to the trend observed offshore. The present difference might be attributed to modern anthropogenic activity (Holmquist- Johnson and Milhous, 2010), mixing of sources on the abyssal plain, or other causes.…”
Section: Discussionmentioning
confidence: 71%
“…This study, completed in cooperation with the U.S. Fish and Wildlife Service Arcata Field Office and the National Fish and Wildlife Foundation, builds upon a substantial amount of previous work (Ayres and Associates, 1999;Hardy and Addley, 2001;Holmquist-Johnson and Milhous, 2010;Bureau of Reclamation, 2011). Collectively, these previous studies summarized the history of anthropogenic impacts, discussed the importance of large flows for reworking channel substrates, and proposed channel-maintenance flows necessary to achieve a range of substrate movement states along the main-stem Klamath River below Iron Gate Dam.…”
Section: Study Reachmentioning
confidence: 99%
“…An additional objective is deterrence of vegetation encroachment, which stabilizes the edge of the low-flow channel and may result in channel narrowing and loss of low-velocity rearing habitat for juvenile salmonids. Shea and others (2016) used sediment entrainment analyses from three independent studies (Ayres and Associates, 1999;Holmquist-Johnson and Milhous, 2010;Bureau of Reclamation, 2011) to define a range of flows necessary to achieve several channel substrate movement states (fig. 3).…”
Section: Study Reachmentioning
confidence: 99%
See 1 more Smart Citation
“…Standing stock of primary producers includes dense beds of filamentous algae and rooted-aquatic plants, such as Cladophora sp., Potamogeton sp., and Elodea sp. Both rooted aquatic plants and filamentous algae create seasonally dense plant and algal patches [53] that are visible from river margins. Primary producer dominance changes longitudinally below the hydroelectric dams, shifting from rooted aquatic plant dominance to filamentous algae dominance downstream.…”
Section: Study Sitesmentioning
confidence: 99%